2013
DOI: 10.1002/bmc.2912
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of conjugated metabolites of drugs in biological matrices after the hydrolysis with β‐glucuronidase and sufatase: a review of bio‐analytical methods

Abstract: Glucuronidation and sulfation represent two major pathways in phase II drug metabolism in humans and other mammalian species. The great majority of drugs, for example, polyphenols, flavonoids and anthraquinones, could be transformed into sulfated and glucuronidated conjugates simultaneously and extensively in vivo. The pharmacological activities of drug conjugations are normally decreased compared with those of their free forms. However, some drug conjugates may either bear biological activities themselves or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…Generally, enzymatic and acid hydrolyses are 2 methods to obtain the free and conjugated forms of fl avonol. Unfortunately, for the acid hydrolysis method, the sample processing is under drastic conditions (heating at 70 °C for 1 h in a thermostatic water bath) thus unstable target analytes cannot always be quantifi ed accurately and completely, which is consistent with our preliminary study (data not shown) [ 30 ] . Therefore, enzymatic hydrolysis method was used to convert the conjugated metabolites into their free forms so that the total myricetin could be quantifi ed.…”
Section: ▼ Methods Developmentsupporting
confidence: 87%
“…Generally, enzymatic and acid hydrolyses are 2 methods to obtain the free and conjugated forms of fl avonol. Unfortunately, for the acid hydrolysis method, the sample processing is under drastic conditions (heating at 70 °C for 1 h in a thermostatic water bath) thus unstable target analytes cannot always be quantifi ed accurately and completely, which is consistent with our preliminary study (data not shown) [ 30 ] . Therefore, enzymatic hydrolysis method was used to convert the conjugated metabolites into their free forms so that the total myricetin could be quantifi ed.…”
Section: ▼ Methods Developmentsupporting
confidence: 87%
“…Moreover, we found sulfated and glucuronidated conjugates of ICT in rat plasma after intravenous administration, indicating that ICA II in rats can be metabolized without the aid of microbial flora in the colon. Sulfated and glucuronidated conjugates of ICT can be quantified using the hydrolysis method with β-glucuronidase and sulfatase [32]; we will present this research in a future paper.…”
Section: Resultsmentioning
confidence: 99%
“…For the purpose of understanding metabolic pathways and overall metabolism of xenobiotics including polyphenolics such as curcumin, hydrolysis with glucuronidase and sulfatase enzymes may be used [47]. Furthermore, the application of enzymatic hydrolysis is useful when authentic reference standards of the conjugates are not available.…”
Section: Discussionmentioning
confidence: 99%